2018
DOI: 10.1038/s41598-018-22164-5
|View full text |Cite|
|
Sign up to set email alerts
|

Lateral attachment of kinetochores to microtubules is enriched in prometaphase rosette and facilitates chromosome alignment and bi-orientation establishment

Abstract: Faithful chromosome segregation is ensured by the establishment of bi-orientation; the attachment of sister kinetochores to the end of microtubules extending from opposite spindle poles. In addition, kinetochores can also attach to lateral surfaces of microtubules; called lateral attachment, which plays a role in chromosome capture and transport. However, molecular basis and biological significance of lateral attachment are not fully understood. We have addressed these questions by focusing on the prometaphase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 78 publications
4
62
0
Order By: Relevance
“…This strongly suggests that interpolar MTs overlap over a broader region in early mitosis, but then become focused at the spindle equator as cells reach metaphase. The broad distribution of antiparallel MTs in early mitosis coincides with CENP-E localization at laterally attached KTs during "prometaphase rosette" configuration (Itoh, Ikeda et al, 2018) (Fig 6A and B, and EV3B), and is consistent with the localization of the antiparallel MT-crosslinker PRC1, which also covers a wider region in prometaphase (Fig EV4B).…”
Section: Cenp-e Is the Predominant Driver Of Mt-flux In Early Prometasupporting
confidence: 79%
“…This strongly suggests that interpolar MTs overlap over a broader region in early mitosis, but then become focused at the spindle equator as cells reach metaphase. The broad distribution of antiparallel MTs in early mitosis coincides with CENP-E localization at laterally attached KTs during "prometaphase rosette" configuration (Itoh, Ikeda et al, 2018) (Fig 6A and B, and EV3B), and is consistent with the localization of the antiparallel MT-crosslinker PRC1, which also covers a wider region in prometaphase (Fig EV4B).…”
Section: Cenp-e Is the Predominant Driver Of Mt-flux In Early Prometasupporting
confidence: 79%
“…The directionality of CENP-E-driven chromosome transport is guided by tubulin detyrosination (Barisic et al, 2015), a modification that is found to be enriched in the equator-oriented microtubules of the mitotic spindle and depleted in the cortical microtubules (Gundersen and Bulinski, 1986). In this way, the combined actions of dynein and CENP-E help to ensure timely chromosome alignment, and also promote the formation of end-on attachments by ensuring incorporation of the chromosomes into the spindle (Itoh et al, 2018) (see poster).…”
Section: Microtubule Capture and Lateral-to-end-on Conversionmentioning
confidence: 99%
“…For example, Ndc80 binding to microtubules is negatively regulated by the RZZ complex in early mitosis, and that inhibition is relieved by recruitment of dynein to the kinetochore (Cheerambathur et al, 2013). The RZZ complex and dynein show dynamic localization to kinetochores, with RZZ localization being highest at nuclear envelope breakdown, and dynein localization being highest later in prometaphase (Itoh et al, 2018). In this way, RZZ-mediated inhibition of Ndc80 likely prevents the formation of stable end-on attachments early in mitosis when there is a high frequency of incorrect kinetochoremicrotubule interactions (Cheerambathur et al, 2013), such as syntelic attachmentswhere both sister kinetochores are attached to the same pole or merotelic attachmentswhere a single kinetochore attaches to microtubules from both spindle poles (see poster).…”
Section: Core Kinetochore-microtubule Interactionsmentioning
confidence: 99%
“…Kinetochore expansion is particularly prominent when mitosis with unattached kinetochores is prolonged by treatment with microtubule depolymerizing drugs [20,21], but kinetochores also expand in unperturbed cells in early prometaphase, when kinetochores are devoid of microtubules [22]. Kinetochore expansion is proposed to make two critical contributions to the fidelity of chromosome segregation: it increases the amount of kinetochore-localized SAC proteins, including Mad1 and Mad2, implying that more MCC can be generated per unattached kinetochore, and it distributes MAPs such as CENP-F, CENP-E and dynein over a larger surface, which facilitates lateral microtubule capture [19,[21][22][23][24]. Consequently, kinetochore expansion is predicted to both expedite the formation of end-coupled kinetochore-microtubule attachments and amplify the checkpoint signal [21,22], which may be particularly relevant when anaphase has to be delayed in the presence of just a few or even a single unattached kinetochore [25].…”
Section: Introductionmentioning
confidence: 99%